Analisis Prosedur Pembuatan Sistem Tata Kerja Bagian Refinery Planning & Optimization Dalam Meningkatkan Kinerja Pada PT Kilang Pertamina Internasional Refinery Unit V Balikpapan - Nurul A’enaya Qalbi; Wira Bharata (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In facing the changes that occur, companies have difficulty following new regulations because of differences with previous regulations. Companies must be able to optimize functions in all parts of the company organization in order to maintain long-term competitiveness and achieve sustainable success. These rules are formed in standard operational procedures which contain operational procedures to ensure consistency, efficiency, minimize errors and safety in every work activity in the company so that it can run effectively and efficiently. This research aims to know the procedures for creating a Work Procedure System at PT Kilang Pertamina International Refinery Unit V Balikpapan and to find out the supporting and inhibiting factors in the procedure for creating a Work Procedure System. This research uses a descriptive qualitative approach. The technique used in this research involved conducting interviews, observation and documentation supported by 2 informants. Based on the results of this research, the procedure for creating a Work System at PT Kilang Pertamina International Refinery Unit V Balikpapan consist of eight structured stages, starting from preparation to the implementation below 1%. The suggestions provided to maximize performance emphasize the importance of effective communication and management commitment to overcoming obstacles in the creation of the Work System at PT Kilang Pertamina International Refinery Unit V Balikpapan.